2015
DOI: 10.1161/circinterventions.115.001847
|View full text |Cite
|
Sign up to set email alerts
|

Selective Proximal Renal Denervation Guided by Autonomic Responses Evoked via High-Frequency Stimulation in a Preclinical Canine Model

Abstract: R esistant hypertension has been linked to chronic excessive sympathetic drive, especially elevation of renal sympathetic activity in some groups of patients.1,2 Against this background, renal artery ablation selectively denervating the kidneys emerges as an alternative treatment for such patients. Although initial trials 3,4 showed promising results with regard to large reductions in blood pressure (BP), disappointingly, the potential therapeutic role of renal denervation (RDN) in lowering BP is being challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 23 publications
3
23
0
Order By: Relevance
“…Furthermore, a postmortem histological study in humans showed that the maximum average number of nerves was observed in the proximal and middle segments of the renal artery and the least number in the distal segments, and the mean distance from the lumen to nerve was highest in the proximal and lowest in the distal segments . Our pervious animal study also found that there was abundant nervous bundle and plexus in middle‐proximal position , and it could be provoked by electrical nerves stimulation and RF current delivery . These findings suggested that middle‐proximal renal artery may be a key site for RDN.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Furthermore, a postmortem histological study in humans showed that the maximum average number of nerves was observed in the proximal and middle segments of the renal artery and the least number in the distal segments, and the mean distance from the lumen to nerve was highest in the proximal and lowest in the distal segments . Our pervious animal study also found that there was abundant nervous bundle and plexus in middle‐proximal position , and it could be provoked by electrical nerves stimulation and RF current delivery . These findings suggested that middle‐proximal renal artery may be a key site for RDN.…”
Section: Introductionsupporting
confidence: 58%
“…Second, the measurement of norepinephrine spillover from the kidney was not performed, so it was not possible to estimate the degree of functional denervation in each group. On this issue, our experimental study in dogs has demonstrated that norepinephrine level reduced by 66% . Third, since all ablations were performed with a saline‐irrigated catheter, it is not certain if similar results would have been obtained with a solid‐tip ablation catheter.…”
Section: Limitationsmentioning
confidence: 97%
“…While PVI has been well recognized as an established ablation approach with clear endpoint using either radiofrequency or cryoenergy in treating AF, RDN currently on the other hand remains at a stage of “blinded ablation.” Several factors such as patient selection, baseline BP patterns, antihypertensive medications, comorbidities, ablation devices, and acute BP response have been reported to be related to the response of RDN . At technique level, electrical stimulation at intraluminal renal artery using electrical catheter aiming at inducing BP elevation measured before and after the ablation procedure has been used to assess the extent of denervation . The stimulation technique may be used as a practical approach to map the renal autonomic nerves adjacent to renal artery and as a guidance to perform “selective renal sympathetic nerve ablation.”…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this study was performed on Chinese Kunming dogs. Using the Chinese Kunming dogs as the experimental animals, we had successfully performed a series of basic researches related to catheter-based RDN technique252728. During the previous peer review procedures of the above published animal studies, the use of Chinese Kunming dogs with “spontaneous” hypertension and natural excessive sympathetic activity had been proposed as a highlights of our researches by several reviewers.…”
Section: Discussionmentioning
confidence: 99%
“…The Chinese Kunming dogs are larger, more aggressive and fierce than beagles, spaniels and mongrels, more importantly having high natural BP and sympathetic activity2526, which are ideal as the experimental animals for renal denervation studies. Using the Chinese Kunming dogs as the experimental animals, we had successfully performed a series of basic researches related to catheter-based RDN technique252728. Prior to conducting experiments in Chinese Kunming dogs, the reasons related to using Chinese Kunming dogs as experimental animals, the source, breeding, feeding conditions, and the experimental protocol of this study was reviewed and approved by the animal experimentation ethics committee of the Chongqing Medical University, following the guidelines of the National Institutes of Health and of the Declaration of Helsinki for the care and use of laboratory animals.…”
Section: Methodsmentioning
confidence: 99%